Survival of cultured allogeneic keratinocytes transplanted to deep dermal bed assessed with probe specific for Y chromosome. Issue 6678 (8th April 1989) - Brain, A.; Purkis, P.; Coates, P.; Hackett, M.; Navsaria, H.; Leigh, I.
Abstract : To determine the survival of cultured allogeneic keratinocytes transplanted to a deep dermal bed 24 tattoos that had been removed by deep shave excision in 19 patients were grafted with sheets of cultured allogeneic keratinocytes from donors of the opposite sex. Cells carrying the Y chromosome were identified in biopsy specimens taken from the graft site by in situ DNA hybridisation with a biotinylated Y probe (pHY 2.1) and visualised with a technique using immunoperoxidase. The cultured allograft sites were biopsied one, two, and three weeks after transplantation. No male cells were identified in any biopsy specimen from female patients who were given transplants of male cultured keratinocytes, and all biopsy specimens from male patients, who received female cultured keratinocytes, showed percentages of male cells within the normal range for male skin. The beneficial effects of cultivated allogeneic keratinocytes result from effects on wound healing other than forming a successful graft that "takes."